Perbedaan Jumlah Produksi ASI Ibu Menyusui Sebelum dan Sesudah Diberikan SULAIKA (Susu Kedelai Katuk) dan Susu Kedelai di Wilayah Kerja Puskesmas Dupak Surabaya - Laurentia Civita Rahma Kusuma (Media Gizi Kesmas, 2023)
Background: The amount of breast milk production is the volume of breast milk that can be produced by a nursing mother every day. The actors that can influence include nutritional intake, psychological conditions, health conditions and history of disease, consumption of milk or breast milk supplements and infant sucking factors. Objectives: The purpose of this study was to analyze the differences in the amount of breast milk produced by breastfeeding mothers before and after being given SULAIKA (Katuk Soybean Milk) in the working area of the Dupak Health Center, Surabaya. Methods: This research was a quasi-experimental research using pre-post control group design. The data were analyzed using the using the Chi-Square statistical test and the data difference test using the Paired t-Test. Results: The normality test in this study indicate that the data to be used is normally distributed. The results of the different test between the volume of breast milk of breastfeeding mothers before and before being given SULAIKA (p = 0.002) and SULE (p = 0.004) showed a significant difference in the amount of milk production. However, there was no significant amount of breast milk production between before SULAIKA was given to SULE with a significant value (p=0.339). Conclusion: There are differences in the amount of breast milk produced by breastfeeding mothers before and after being given SULAIKA or Katuk Soy Milk as well as the amount of milk production before and after being given SULE or Soy Milk. Selection of food ingredients that have the potential to increase the amount of breast milk production is suggested as an effort to increase milk production.